Environmental Health Education in Schools as Strategy for Rodent Control: An Experience in a Shantytown of Buenos Aires, Argentina - Hancke, Diego (2014)
The general aim of this study was to assess the possibility of including elements of environmental health education within the curriculum of a school located in a shantytown of Buenos Aires city, Argentina. An environmental health education campaign was designed to introduce school-aged children to the problems posed by the lack of environmental sanitation, by using rodents as indicators of environmental disorder. The methodology implemented consisted of a lecture and two practical activities where the participating children were the evaluators of their neighborhood environment, recording the environmental factors that indicate direct or indirect presence of rodents and carrying out a survey about rodents among their neighbors. To assess the impact of the activities, an anonymous questionnaire was performed with the students before and after the campaign. The results showed that students were able to identify the man-made factors which favor the presence of rodents and were encouraged to propose strategies related to environmental sanitation to reduce rodent proliferation and the transmission of their parasites. This study demonstrated the feasibility of performing environmental health education campaigns in school-aged children by using practical activities to stimulate observation, participation, and comprehensive understanding of the problems posed by urban pests.